The Effect of Humor Therapy on Increasing Elderly Self Esteem at UPT Tresna Wreda Social Services Jombang - Nugroho, Muhamad Adjie Pramono; Yani, Athi’ Linda; Mukarromah, Indah (Promotion and Prevention in Mental Health Journal, 2023)
In the elderly, it can cause various general and specific problems; several causes cause multiple issues in the elderly, such as biological, psychological, social, and spiritual conditions. The purpose of this study was to determine the effect of humor therapy on the level of self-esteem of the elderly. Pre-Experimental Research Design One Group Pre-Post Test Design approach, using Nonprobability sampling technique with the purposive sampling method. The number of participants in this study was 30 who had lived in the orphanage for less than six months, had experienced HDR, and were not deaf or blind. Humor therapy is given for one time in 30 minutes. The therapy instrument used the SOP and RSES questionnaire. The test analysis used was a Paired T-test (α 0.05). The results showed the level of self-esteem of the elderly before humor therapy. After humor therapy, there was an increase in self-esteem from a median of 13 to 16. There is a significant effect after being given humor therapy with a P value (0.00) < α. Humor therapy interventions can significantly be used as an alternative to increasing the self-esteem of the elderly. Humor film shows stimulate respondents to relax and improve mood, and can reduce depression.